Is the Peripheral Zone Thickness an Indicator of a Learning Curve in Bipolar Transurethral Plasma Enucleation of the Prostate?—A Single Center Cohort Study - Wang, Qihua; Alshayyah, Rami; He, Yi; Wen, Lijie; Yu, Yang; Yang, Bo (Frontiers in Surgery, 2022)
Background We conducted this cohort study to assess the differences in the learning curve of bipolar transurethral plasma enucleation of the prostate (B-TUEP) associated with prostatic peripheral zone thickness (PZT) under MRI quantitative measurements. Methods For the study, 60 patients with benign prostatic hyperplasia (BPH) were involved. PZT are defined as “Thin” (<7 mm), “Thick” (>10 mm), and “Medium” (in between), with 20 patients in each group. Learning stages were defined as Group 1 (No. 1–20), Group 2 (No. 21–40), and Group 3 (No. 41–60). We measured parameters of the prostate, such as PZT and transitional zone thickness (TZT), with MRI. A learner with no experience in enucleation performed the operations. Statistical analyses were performed to compare the differences. Pearson correlation analysis and multiple linear regression analysis evaluated the relationship between characteristics of patients. P < 0.05 was deemed statistically significant. Results One-Way ANOVA revealed different enucleation efficiency (0.811 ± 0.18 vs. 0.748 ± 0.14 vs. 0.634 ± 0.16), prostate volume (58.9 ± 15.33 vs. 57.3 ± 15.58 vs. 46.6 ± 14.10), and thickness of transition zone (44.45 ± 7.60 vs. 42.45 ± 6.08 vs. 34.78 ± 6.04) among Thin, Medium, and Thick groups. The enucleation efficiency is different between groups divided by learning stages (Group 1 vs. Group 3, 0.658 vs. 0.783; Group 2 vs. Group 3, 0.751 vs. 0.783). Pearson correlation analysis reveals that PZT was negatively correlated with prostate volume (r = −0.427), resection weight (r = −0.35), enucleation efficiency (r = −0.445), and TZT (r = −0.533), and was positively correlated with Q-max (r = 0.301) and bladder outlet obstruction index (BOOI) (r = 0.388). The regression coefficients of PZT, TZT, prostate volume, and Q-max were −0.012, 0.008, 0.007, and 0.013, respectively (all P < 0.05). Conclusion Lower PZT is independent of higher enucleation efficiency, larger adenoma, and higher TZT. PZT may be an important factor on the learning curve of B-TUEP. Higher TZT, prostate volume. and Q-max may also relate to higher enucleation efficiency. For B-TUEP learners, it seems easier to perform the operation when the PZT is low, though more care should be taken with the capsule perforation. Further, the capsule plane should be maintained more attentively if the PZT is high.